“L’arte vale più della verità”: Riflessioni estetiche sulla volontà di potenza - Giacomelli, Alberto (Scenari, 2021)
This essay intends to investigate the particular aesthetic meaning of the “Will to Power”. The first part of the article aims to bring out some of the principal meanings of this complex and controversial notion of Nietzsche, by comparing it to the theories of conatus in Spinoza, Wille in Schopenhauer, and Es in Freud. In the second part, the article refers to Heidegger’s Nietzsche (in particular to the first section of this work, Will to Power as Art) as a pivotal source to understand Nietzsche’s assertion “Art is worth more than truth”. Heidegger identifies the Will to Power as the hermeneutic heart of Nietzsche’s thought, understood as the extreme ending point of Western metaphysics. On that basis Heidegger analyses Nietzschean aesthetics and investigates the role of the artist, the relationship between art and physiology, art and nihilism, art and truth, as well as the theme of intoxication as a creative condition par excellence. Starting from this interpretation, and in particular from Heidegger’s five theses on art, this article aims to display how art represents for Nietzsche the great stimulant of life for Nietzsche. Than it will be underlined how art as Will to Power stands in sharp contrast to the Platonic hierarchy between sensible and supra-sensible, promoting a liberating and radical perspectivism.